Kondisi Umum dan Pemicu Terjadinya Pergolakan Yaman - Setiawati, Debi; Rahayu , Hesti Rika; Arbakafin, Yuni (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
The political dynamics in the Middle East region have always been a global concern. The high complexity of tensions mixed with various issues, both regional and global, has become a yearly conflict that is always present in the public eye. The various conflicts in the oil-rich region occurred both due to factors between countries, internal parties and the intervention of external parties. Including the turmoil of the prolonged conflict, never ending, and also capturing a lot of world attention are the conflicts in Syria and Yemen which are thick with Sunni Shia sectarian issues. Yemen is one of the countries in the Middle East that is currently experiencing upheaval. In addition, Yemen is currently experiencing the turmoil of conflict and civil war which has now made the country the poorest country in the Arabian Peninsula and has been on the brink of famine. The war cut transportation routes for aid, food and fuel, which then led to reduced imports and gave birth to severe inflation. The Yemeni people have lost their jobs, because wages are not being paid. The conflict forced them out of their jobs and homes to flee. The United Nations reports that two-thirds of all districts in both Saudi Arabia and Iran are present and jockeying for influence in the conflicts in Syria and Yemen. In the conflict in Syria and Yemen, apart from having an impact on political stability. For example, the presence of Israel has contributed to the situation in the conflicts in Syria and Yemen. In the conflict in Yemen. Where a sense of common identity, background and history complements the further interests of external countries involved, whether it concerns the exploitation of natural resources or is geopolitical, hegemonic and territorial expansion. The influence of the Region will certainly have a major impact on the development of the country's internal and external political system. Yemen has become a country with the worst humanitarian crisis in the world. The World Food Program (WFP) notes that after five years of constant war, 20 million people in Yemen are starving. This type of research is quantitative using descriptive methods. The purpose of this descriptive research with a quantitative approach is to explain a situation that is to be studied with the support of literature studies so that it further strengthens the researcher's analysis in making a conclusion. Descriptive itself is a type of research on a situation objectively starting from data collection, interpretation of the data as well as the appearance and results.